Case Report: Extra-adrenal retroperitoneal paraganglioma in a young adult cat diagnosed by imaging, pathology, and immunohistochemistry - Sohn, Sang-June; Lim, Sohee; Park, Junghoon; Choi, Ulsoo; Hong, Yeon-Jung (Frontiers in Veterinary Science, 2025)
Paragangliomas are rare neuroendocrine tumors arising from paraganglionic tissues associated with the autonomic nervous system. Although they are uncommon in veterinary medicine, particularly in cats, accurate diagnosis is essential due to their potential malignancy. An 18-month-old neutered male domestic shorthair cat presented with a retroperitoneal mass near adrenal glands. Computed tomography revealed an irregular, mildly contrast-enhancing mass abutting both adrenal glands and displacing adjacent vessels. Fine-needle aspiration cytology suggested a malignant round cell tumor with differential diagnosis of lymphoma, nephroblastoma, or primary embryonal tumor. Surgical excision was performed and histopathological examination identified a high-grade round cell neoplasm with a high mitotic index. A broad panel of immunohistochemistry excluded lymphoma and nephroblastoma, confirming extra-adrenal paraganglioma based on strong positivity for anti-synaptophysin, neuron-specific enolase, chromogranin A, and cytokeratin 19 antibodies. On postoperative day two, the cat developed suspected cranial mesenteric artery thrombosis leading to mesenteric ischemia and eventually euthanasia due to poor prognosis. This case emphasizes the importance of considering extra-adrenal paraganglioma in differential diagnoses of retroperitoneal masses in young cats and highlights the critical role of advanced imaging and immunohistochemistry in achieving definitive diagnosis.